Neuroprotective Effects of Bacterial Melanin in a Rotenone-Induced Parkinson’s Disease Rat Model: Electrophysiological Evidence from Cortical Stimulation of Substantia Nigra Neurons - John Sarkissian; Michael Poghosyan; Margarita Danielyan; Narek Makaryan; Tigran Petrosyan; Sona Avetisyan; Anichka Hovsepyan (Biomedicines)
Background/Objectives: As the regulatory center for basal ganglia, the substantia nigra is involved in the pathophysiology of dopaminergic dysregulation in Parkinson’s disease (PD). Increasing neuronal excitability of dopaminergic neurons by different therapeutic methods could reverse the locomotor disturbances of PD. The purpose of this study was the comparative assessment of effects induced by excitatory output from the motor cortex to the substantia nigra (SN) and to investigate the pattern of neuronal responses in an experimental rat model of rotenone-induced (intracerebral infusion) neurodegeneration and treated with bacterial melanin (BM). Methods: Thirty-three rats were divided into three groups: control or intact animals (n = 12), animals with the rotenone-induced model of PD (n = 10), and animals with the PD model and treated with BM in 48 h following the infusion (n = 11). Registration of neuronal activity from SN neurons was conducted at four weeks following the rotenone administration. High-frequency stimulation of brain cortical area M1 was performed and the background and evoked activity patterns of 622 neurons were recorded. The difference between the groups was analyzed using one-way ANOVA followed by Tukey’s test. Results: A statistically significant difference was observed between the similar proportions of post-stimulus effects registered in different groups, showing the predominance of excitatory responses in the neurons of the melanin-treated group. A comparison of the firing pattern between the SNc and SNr neurons did not reveal significant differences. Conclusions: BM treatment has the potential to enhance motor recovery after neurodegeneration in the SN. Deep brain stimulation via the cortico-nigral pathway, with the application of BM, enhances electrical activity in dopaminergic neurons of the substantia nigra and could be a potential therapeutic model for PD.